The prevalence of substance use among adolescents and its correlation with social and demographic factors - Rakić, Dušica B.; Rakić, Branislava; Milošević, Zoran; Nedeljković, Ivan (Vojnosanitetski pregled, 2014)
Backround/Aim. Adolescence is the period of greatest risk of starting to use substances: cigarette smoking, alcohol and illicit drugs. In the first decade of this millennium substance use among adolescents has increased. The aim of this study was to explore the prevalence of substances use among adolescents and its correlation with social and demographic factors. Methods. The study was conducted among adolescents in Novi Sad during 2010–2011 and included 594 conveniently selected adolescents (275 male and 319 female), aged 15–19 years. A special questionnaire was used and statistical analysis performed in SPSS17. The correlation between parameters was evaluated by the Pearson correlation method and frequency differences were analysed using χ2 test and starting level was p < 0.05. Results. The prevalence of substance use was statistically higher in males. Cigarettes were smoked daily by 21.45% males and 15.67% females (p < 0.01), alcohol was consumed by 81.6% males and 69.11% females (p < 0.001) and illicit drugs were used by 13.65% males and 8.30% females (p < 0.05). There was a positive correlation between smoking cigarettes and alcohol consumption, but negative between smoking cigarettes and the use of illicit drugs (p < 0.01). The prevalence of substance use was statistically higher among adolescents with poor achievement in school (p < 0.01), who lived in a broken home (illicit drugs p < 0.01) and who had more pocket money (cigarette smoking p < 0.01, and alcohol consumption p < 0.5). Conclusion. Stable family, lower amount of pocket money weekly and good school performance are protective factors in prevention of substances use among adolescents.
Keywords: substance related disorders; adolescent; smoking; alcohol drinking; street drugs; risk factors